2016
DOI: 10.1097/aud.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinguistic Outcome Measures in Adult Cochlear Implant Users Over the First Year of Implantation

Abstract: Objectives Post-lingually deaf cochlear implant users’ speech perception improves over several months after implantation due to a learning process which involves integration of the new acoustic information presented by the device. Basic tests of hearing acuity might evaluate sensitivity to the new acoustic information and be less sensitive to learning effects. It was hypothesized that, unlike speech perception, basic spectral and temporal discrimination abilities will not change over the first year of implant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…Measures of spectral resolution have been shown to strongly correlate with open-set speech understanding in both post-lingually deaf adult CI users (Henry and Turner, 2003;Henry et al, 2005;Won et al, 2007;Saoji et al, 2009;Green et al, 2014;Winn and Litovsky, 2015) as well as in pre-lingually deaf school-age children with CIs (Jung et al, 2012). Although various approaches have their merits, SRD is an efficient method to test spectral resolution that does not require any knowledge of phonemic or linguistic structure (Drennan et al, , 2016. In SRD, listeners discriminate between two spectrallymodulated noise stimuli with shifted spectral envelope phases (Supin et al, 1994a(Supin et al, , 1994b(Supin et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Measures of spectral resolution have been shown to strongly correlate with open-set speech understanding in both post-lingually deaf adult CI users (Henry and Turner, 2003;Henry et al, 2005;Won et al, 2007;Saoji et al, 2009;Green et al, 2014;Winn and Litovsky, 2015) as well as in pre-lingually deaf school-age children with CIs (Jung et al, 2012). Although various approaches have their merits, SRD is an efficient method to test spectral resolution that does not require any knowledge of phonemic or linguistic structure (Drennan et al, , 2016. In SRD, listeners discriminate between two spectrallymodulated noise stimuli with shifted spectral envelope phases (Supin et al, 1994a(Supin et al, , 1994b(Supin et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Although spectral ripple discrimination has recently been shown to be a promising clinical marker of auditory acuity in adult, post-lingually deaf, CI users (Drennan et al 2014, Shim et al 2014, Drennan et al 2015), little is known about how performance on this measure changes with development. Although spectral resolution might prove to be a relatively stable and acute measure of device efficacy for adults, it is important to understand how spectral resolution is affected by development before measures of spectral resolution can be applied effectively to young listeners with CIs.…”
Section: Discussionmentioning
confidence: 99%
“…Spectral resolution has shown promise as a proxy measure of speech perception to assess device candidacy and measure effectiveness of signal processing strategies (Drennan et al 2014, Shim et al 2014, Drennan et al 2015). Given that spectral resolution is robustly related to speech perception for adult CI listeners, some investigators have suggested that it could be useful for testing device efficacy in infants with CIs or HAs who are too young for clinical measures of speech perception (Won et al 2011, Drennan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been shown that better spectral resolution correlates with better speech recognition in noise for CI users (Drennan et al 2016; Henry & Turner 2003; Holden et al 2016; Won et al 2007; however, see Langner et al 2017). It has also been shown that simulating broad activation patterns in normal hearing listeners via a vocoder results in deterioration of both spectral resolution and vowel recognition (Litvak et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that simulating broad activation patterns in normal hearing listeners via a vocoder results in deterioration of both spectral resolution and vowel recognition (Litvak et al 2007). Additionally, spectral resolution tests involve minimal learning (Drennan et al 2016; Won et al 2007), indicating the potential use for these tests after remapping in predicting which adjustments may result in optimal speech perception in noise.…”
Section: Introductionmentioning
confidence: 99%